On the asymptotic behavior of delay differential equations a n d i t s r e l a t i o n s h i p w i t h Co- s e m i g r o u p - Chau, Dang Dinh; Cuong, Nguyen Bui (VNU Journal of Science: Mathematics - Physics; Vol 23 No 2, 2007)
A b s t r a c t . In this paper, we study the asymptotic behavior o f linear diíĩerential equations under nonlinear pcrturbation. Lct’s considcr the dclay diíĩerential equations: ^ = A x + f(t,Xị), whcre t G / ĩ + , A e C(E)} f : R+ X E — ► E and {T(t))t> 0 is Co-semigroup be generated by A. Wc will give some suffìcicnt conditions for uniĩormly stable and asymptotic equivalence of above equations.